Traffic Assessment for Unsignalized Intersection Under Influence for Side Friction on Padang Lawas, North Sumatera - Muchammad Zaenal Muttaqin; Desi Yanti Futri Citra Hasibuan (Jurnal Inovasi Teknologi, 2020)
An unsignalized intersection is a part of a road where currents from different directions or directions meet. There was a conflict between currents from theopposite direction and intersecting each other, resulting in congestion along the arms of the intersection. Likewise, at the intersection of four arms without a signal at Sibuhuan Market, Padang Lawas Regency, North Sumatra, there is a congestion caused by the reduction in the effective width of the road due to parking on the road. At the intersection of four arms without a signal at Sibuhuan Market, Padang Lawas Regency, North Sumatra, there is a congestion caused by side obstacles, a high vehicle population that is not matched by the availability of adequate infrastructure so this research aims to analyze the performance of the four-arm intersection without a signal. based on Indonesian Highway Capacity Manual (MKJI 1997) and analyzes them to improve the performance of these unsignalized intersections. The analysis of the results showed that the intersection performance for the unsigned intersection conditions in the existing condition with the parking on the side of the road which reduced the effective width, the maximum total flow was 2341 pcu / hour, capacity (C) = 2707.06 pcu / hour, and the degree of saturation (DS) = 0.86, intersection delay (D) = 14.62 seconds / pcu and queuing opportunity (QP) 30.03 - 59.32%. Therefore, it is necessary to recalculate with various alternatives so that the DS value meets the requirements of the Indonesian Highway Capacity Manual, which is < 0.75.